Economic Tools to Support Socio-Cultural Projects ("Journal "U". Economy. Management. Finance.", 2021)
The article considers the main directions in the development of modern investment policy and grant support of social projects. The analysis of state programs to support social entrepreneurship in the territory of the Russian Federation is carried out.
Keywords: social entrepreneurship, investment policy, grant support, sociocultural design.; social entrepreneurship